Diagnosis of metaplastic synovial cysts in clinical dermatology - Paayal S. Vora; Sonam Rama; Stephen Olsen (Wiley, 2023)
Abstract Metaplastic synovial cysts are a rare clinical finding, with less than 70 cases diagnosed to date. These cysts are painful and can greatly impact patients' quality of life. The goal of this case report is to describe the manifestations of these cysts to aid in clinical diagnosis and management. We herein report a case of a 58‐year‐old male who presented with a bump on the lateral left knee. He experienced pain upon walking. Notably, he had a past medical history of left knee replacement 15 years prior to presentation. Upon physical exam, the bump resembled a firm subcutaneous nodule. It was subsequently biopsied via eight‐mm punch excision, revealing a metal portion of the patient's knee replacement; biopsy resulted in the removal of the entire bump. Biopsy results showed a cystic space in the deep dermis containing papillary villous projections consisting of fibrous cores, partially surfaced by a synovial‐like lining. Based on these results, a metaplastic synovial cyst was diagnosed. The patient was referred to orthopaedic surgery for replacement to prevent recurrence, as the metal in the knee replacement was presumed the source of the cyst. The patient was then reassessed 3 months later, and he described resolution of his knee pain. Physical exam showed a well‐healed linear scar. This patient's history and exam findings, along with the dermatopathology results, reflect the characteristic pattern in patients suffering from metaplastic synovial cysts. Prompt identification and subsequent removal can significantly improve patient's pain and ability to carry out daily activities.